2012
DOI: 10.1007/s00339-012-6791-z
|View full text |Cite
|
Sign up to set email alerts
|

Novel methods for synthesizing halide-free alane without the formation of adducts

Abstract: Many of the current synthesis methods for aluminum hydride (alane-AlH 3 ) involve reacting AlCl 3 and LiAlH 4 in solvents. The reaction requires the formation of an alane adduct such as AlH 3 ·[(C 2 H 5 ) 2 O] prior to obtaining crystallized stable α-AlH 3 . This process requires several hours of pumping in a vacuum system to remove the ether and convert the alane etherate into stable α-alane. This crystallization process is both costly and hazardous because a large amount of highly flammable material (e.g. et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…The synthesis method described above requires the use of a large amount of solvents such as ether and the removal of such solvents is both costly and hazardous. Dinh et al [74] presented a novel method to synthesize adduct-free AlH 3 . They directly heated the mixtures of LiAlH 4 and AlCl 3 at 75 °C in the solid state.…”
Section: Synthesis By the Desolvation Of Etherate Alhmentioning
confidence: 99%
“…The synthesis method described above requires the use of a large amount of solvents such as ether and the removal of such solvents is both costly and hazardous. Dinh et al [74] presented a novel method to synthesize adduct-free AlH 3 . They directly heated the mixtures of LiAlH 4 and AlCl 3 at 75 °C in the solid state.…”
Section: Synthesis By the Desolvation Of Etherate Alhmentioning
confidence: 99%
“…LiAlH4 and AlCl3 although alternative electrochemistry, [202] organic adducts, [203] and solvent free methods [204] have been developed. In the current state, AlH3 may be suitable for hydrogen generation at low temperatures, although its cost effective regeneration could be problematic.…”
Section: High Capacity Aluminium Containing Compoundsmentioning
confidence: 99%
“…Processing and chemical related challenges associated with traditional methods, such as precise temperature control, handling of volatile organic liquids and significant loss of yields have prompted development of other syntheses routes that (1) may afford adduct-free alane [18][19][20][21][22][23][24] and (2) utilize small amounts solvents or are entirely solvent-free [13][14][15][16][17]. We and others have recently demonstrated that these shortcomings can be partly circumvented by solvent-free mechanochemical syntheses of alane at room temperature using LiH or LiAlH4 and AlCl3 [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%